Identifying Surrogates for Heart and Ipsilateral Lung Dose to Guide Field Placement and Treatment Modality Selection during Virtual Simulation of Breast Radiotherapy. Issue 4 (April 2021) - Wickers, S.; Thould, C.; Keeble, J.; Bodey, R.; Harsanyi, C.; Royle, G.; Gaze, M.N.
Abstract: Aims: Virtual simulation (VSim) of tangential photon fields is a common method of field localisation for breast radiotherapy. Heart and ipsilateral lung dose is unknown until the dosimetric plan is produced. If heart and ipsilateral lung tolerance doses are exceeded, this can prolong the pre-treatment pathway, particularly if a change of technique is required. The aim of this study was to identify predictive surrogates for heart and ipsilateral lung dose during VSim to aid optimum field placement and treatment modality selection. Materials and methods: Computed tomography data from 50 patients referred for left breast/chest wall radiotherapy were retrospectively analysed (model-building cohort). The prescribed dose was 40.05 Gy in 15 fractions using a tangential photon technique. The heart and ipsilateral lung contours were duplicated, cropped to within the field borders and labelled heart-in-field (HIF) and ipsilateral lung-in-field (ILF). The percentage of HIF (%HIF) and ILF (%ILF) was calculated and correlated with mean heart dose (MHD) and volume of the ipsilateral lung receiving 18 Gy (V18Gy ). Linear regression models were calculated. A validation cohort of 10 left- and 10 right-sided cases with an anterior supraclavicular fossa (SCF) field, and 10 left- and 10 right-sided cases including the internal mammary nodes using a wide tangential technique and anterior SCF field, tested the predictive model. Threshold values for %HIF and %ILF were calculated for clinically relevant MHD and ipsilateral lung V18Gy tolerance doses. Results: For the model-building cohort, the median %HIF and MHD were 2.6 (0.4–16.7) and 2.3 (1.2–8) Gy. The median %ILF and ipsilateral lung V18Gy were 12.1 (2.8–33.6) and 12.6 (3.3–35) %. There was a statistically significant strong positive correlation of %HIF with MHD ( r 2 = 0.97, P < 0.0001) and of %ILF with ipsilateral lung V18Gy ( r 2 = 0.99, P < 0.0001). For the validation cohort, the median %HIF and MHD were 3.9 (0.6–8) and 2.5 (1.4–4.7) Gy. The median %ILF and ipsilateral lung V18Gy were 20.1 (12.4–32.0) and 20.9 (12.4–34.4) %. The validation cohort confirmed that %HIF and %ILF continue to be predictive surrogates for heart and ipsilateral lung dose during VSim of left- and right-sided cases when including the SCF ± internal mammary nodes with a three-field photon technique. Discussion: The ability to VSim breast radiotherapy (±nodal targets) and accurately predict the heart and ipsilateral lung doses on the dosimetric plan will ensure that tolerance doses are not exceeded, and identify early in the pre-treatment pathway those cases where alternative techniques or modalities should be considered. Highlights: Virtual simulation of breast radiotherapy (±nodes) in the absence of dose surrogates may lead to unnecessary compromise to target coverage or the heart and/or ipsilateral lung dose being exceeded on the optimised plan. Predicting heart and lung dose during virtual simulation will improve efficiency. Percentage of heart-in-field is an accurate surrogate for mean heart dose during virtual simulation. Percentage of lung-in-field is an accurate surrogate for ipsilateral lung V18Gy during virtual simulation.